Analisis Implementasi Kurikulum Merdeka di Madrasah Piloting MIN 2 Bantul Yogyakarta - NUR ZAKIYAH; MUHAMMAD WASITH ACHADI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
The purpose of this study is to analyze the implementation of the independent curriculum in the MIN 2 Bantul piloting madrasah, Yogyakarta. With qualitative types of research phenomenological approach. The location of this research was conducted at MIN 2 Bantul Yogyakarta. The source of the data of this study is informants. With the subject of research 1 person principal madrasah MIN 2 Bantul. Data collection techniques through observation, interviews and documentation, the results of this study the implementation of an independent curriculum in the MIN 2 Bantul piloting madrasah have not been fully implemented. Because there has been no follow-up from the Ministry of Religious Affairs. The school also has its own initiatives to make independent curriculum training and also learn from several elementary school teachers who have implemented the independent curriculum.